Public Awareness, Knowledge, and Attitudes Towards Digital Health Insurance Platforms in Bahrain: A Mixed-Methods Study - Salim Hasan AL ARRAYED (Multidimensional Research Insights, 2026)
Background: Digital health insurance platforms represent key health informatics tools in Bahrain, promising enhanced healthcare access through IT integration. Despite mandatory insurance and 99% internet penetration, adoption remains low, underscoring informatics barriers in user-technology interactions. Objective: This informatics-focused study identified predictors of digital health insurance platform adoption and explored user perceptions, trust dynamics, and barriers among Bahrain residents using mixed-methods analytics. Methods: A convergent mixed-methods design integrated quantitative and qualitative informatics approaches. A crosssectional survey (n=300; stratified random sampling) measured sociodemographics, awareness, perceived usefulness (α=.742), ease of use, trust, cost perception, current use, and behavioral intentions via 5-point Likert scales. Analyses included descriptive statistics, χ² tests, t-tests, Pearson correlations, and binary logistic regression (Nagelkerke R² for model fit). Twelve semi-structured interviews (purposive sampling to thematic saturation) underwent inductive thematic analysis to uncover informatics-related themes. Results: Of 300 respondents, 52% (n=156) were active users. Key TAM constructs showed moderate favorability: Perceived Usefulness (M=3.53±1.09), Ease of Use (3.42±1.19), Trust (3.38±1.17), with Behavioral Intention more variable (3.07±1.32). Awareness linked to current use (χ²=9.84, p=.002, V=.181); trust strongly predicted future intention (χ²=44.27, p<.001, V=.384; r=.51, p<.001) and usefulness differentiated users vs. non-users (t=2.79, p=.006, d=0.32). Logistic regression confirmed trust (OR=1.62, p<.001), awareness (OR=1.83, p=.036), and ease of use (OR=1.33, p=.015) as adoption predictors (R²=.148); demographics were nonsignificant. Six qualitative themes emerged on informatics barriers. Conclusions: Trust emerges as the primary informatics driver of digital health insurance adoption in Bahrain, extending TAM for health IT systems in GCC contexts. Informatics interventions should target trust enhancement, user interface simplification, and stakeholder decision support strategies.